Key access and utilization descriptors for chickpea genetic resources - Bioversity International; International Center for Agricultural Research in the Dry Areas; International Crops Research Institute for the Semi-Arid Tropics; Indian Agricultural Research Institute (2010)
This minimum list consists of an initial set of characterization and evaluation descriptors for chickpea utilization.